Attributes of Cannabis Exhibition Selected by Consumers in Bangkok Metropolitan - chokdee, Pitchaya; Nonthanathorn, Phiphat (Journal of the Association of Researchers, 2024)
The objectives of this research were to 1) examine the relationship between personal demographics and the behaviors of consumers interested in attending a cannabis expo who live in Bangkok 2) examine the relationship between personal demographics and the characteristics of the cannabis expo selected by consumers who live in Bangkok 3) examine the characteristics of the cannabis expo selected by consumers who live in Bangkok. The target population of this research was 450 people living in Bangkok, who were interested in attending a cannabis exhibition. This research was conducted using questionnaires. The data were analyzed using the chi-square test method. The majority of the sample were female, aged 31-40 years, single, with a bachelor’s degree or equivalent education, employed in the private sector, and most average monthly income of 20,001- 30,000 bath.. The result showed that 1) gender, education, and average monthly salary were related to the behavior of consumers interested in exhibiting cannabis and living in Bangkok.2) The personal demographic factors the differentiation of personal demographic factors had an impact on the important level of the characteristics of the cannabis expo selected by consumers who live in Bangkok in all aspect, especially for the aspect of location, which is large and easy to transport and park.